Influence of New Compound Disinfectant From N-Dodecyl-2-(Piridin-1-Ium)Acetamide Chloride on Pathogenic Microorganisms in Poultry Houses - Chen, Nannan; Qin, Pingwei; Liu, Yu; Yang, Ying; Wen, Hairuo; Jia, Lihua; Li, Jing; Zhu, Zhanbo (Frontiers in Microbiology, 2021)
With the development of large-scale and intensive poultry farming, environmental disinfection has become particularly important, and the effectiveness of disinfection depends upon the performance of the disinfectants. Quaternate ammonium salt is a group of positively charged polyatomic ions with both antibacterial and antiviral activities. In order to prepare an ideal disinfectant for poultry farms, we combined a quaternate ammonium salt N-dodecyl-2-(piridin-1-ium)acetamide chloride with two other disinfectants (chlorhexidine acetate and glutaraldehyde), respectively. The antimicrobial activity, mutagenicity, and safety of the compound disinfectants were assessed by European Standard methods using ATCC strains and clinical isolates. The results showed that both compound disinfectants meet the requirements of microbial reduction, and their effectiveness was not affected by organic matter. Quaternary ammonium disinfectant resistance genes were not detected in the strains tested indicating that bacteria are less likely to develop resistance to these compound disinfectants. Ames test showed that there was no detectable mutagenicity in the strains treated with the compound disinfectants. In vivo experiment showed that both compound disinfectants did not have significant pathological effect in mice. The bactericidal effect of the compound disinfectants was not significantly different among strains of different sources (p > 0.05). Clinical tests showed that compound disinfectant had a good bactericidal effect on the air and ground of poultry farms. These results show that quaternary ammonium salts in combination with other compounds can enhance the bactericidal effect and can be used safely in poultry feedlots. This study provides a technical reference for the development of a new quaternate ammonium compound disinfectant with strong disinfection effect and low irritation.